Development of nutrition of sunflower with sewage sludge and nitrogen - Lobo, Thomaz Figueiredo [UNESP]; Filho, Helio Grassi [UNESP]; Bull, Leonardo Theodoro [UNESP]; Kummer, Ana Carolina Barbosa [UNESP]; De Souza, Flavia Luize Pereira (Centro Universitario de Maringa, 2019)
The influence of composted sewage sludge and nitrogen in nutrition factors and the development of sunflower crops after the sixth application in crop rotation are evaluated. The experiment was conducted on the Experimental Farm São Manuel, Faculty of Agronomic Sciences of UNESP in Botucatu SP Brazil. Experimental design comprised randomized blocks with 6 treatments and 4 replications: T0 - without nitrogen fertilization; T1 - synthetic nitrogen fertilization; T2 - 50% nitrogen fertilization derived from sewage sludge and 50% in synthetic form; T3 - 100% nitrogen fertilization from sewage sludge; T4 - 150% nitrogen fertilization from sewage sludge; T5 - 200% nitrogen fertilization from sewage sludge. Composted sewage sludge increased N, P, S, Fe, Mn and Zn rates in leaves and a greater export of all nutrients. Chemical nitrogen fertilization decreased K and increased B, Fe and Mn in the leaf and an increase in the export of all nutrients. Composted sewage sludge and nitrogen fertilizer increased plants' height, stalk diameter, number of leaves and chapter diameter.
Desenvolvimento e nutrição do girassol com lodo de esgoto e nitrogênio
Keywords: Biotic factors; Export of nutrients; Organic agriculture; Sustainability